2005
DOI: 10.1136/adc.2004.060434
|View full text |Cite
|
Sign up to set email alerts
|

Potential risk factors for the development of acute renal failure in preterm newborn infants: a case-control study

Abstract: Aims: To determine in a case-control study possible associations between the development of acute renal failure in preterm newborns and therapeutic interventions, particularly drug treatments. Methods: The study population was 172 preterm infants of ,38 weeks gestation; 71 had acute renal failure and 101 were controls closely matched for gestational age and birth weight. Maternal and neonatal information was collected for both groups through questionnaires and interviews. Routine data on renal variables were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
138
2
17

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(174 citation statements)
references
References 24 publications
17
138
2
17
Order By: Relevance
“…Prolonged exposure to antibiotics and the use of indomethacin were independent factors associated with an increased risk of renal dysfunction/failure. The risk factors we identified that are associated with renal dysfunction are similar to those previously reported, 1,3,5 and some of these risk factors are potentially modifiable. Cataldi et al 5 showed that low birth weight, maternal exposure to more drugs during pregnancy and delivery (mainly antibiotics and nonsteroidal anti-inflammatory drugs), low Apgar scores and patent ductus arteriosus were the risk factors for renal failure in low-birth-weight infants.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Prolonged exposure to antibiotics and the use of indomethacin were independent factors associated with an increased risk of renal dysfunction/failure. The risk factors we identified that are associated with renal dysfunction are similar to those previously reported, 1,3,5 and some of these risk factors are potentially modifiable. Cataldi et al 5 showed that low birth weight, maternal exposure to more drugs during pregnancy and delivery (mainly antibiotics and nonsteroidal anti-inflammatory drugs), low Apgar scores and patent ductus arteriosus were the risk factors for renal failure in low-birth-weight infants.…”
Section: Discussionsupporting
confidence: 82%
“…[1][2][3][4][5][6][7][8] This complexity is highlighted by how the terms 'renal dysfunction' and 'renal failure' are used in our data set. Only 15% of infants with any creatinine X1.3 mg per 100 ml and 33% of infants with any creatinine X2.0 mg per 100 ml were identified as having 'renal problems.'…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In neonates with AKI, mortality rate ranges from 33% up to 78% (1)(2)(3)(4). AKI is an independent predictor of mortality in critically ill newborns.…”
mentioning
confidence: 99%